Caracterizacion del uso de la tierra y bosques secundarios en la llanura aluvial inundable de la zona Muyuy-Iquitos, Amazonia Peruana - Freitas-Alvarado, L.; Baluarte-Vasquez, J.; Kop, P. van de; Inga-Sanchez, H.; Jong, W. de; Melendez, W.; Salazar Vega, A. (2000)
Results based on a socioeconomic survey on flood plain forest fallows are presented. The study was aimed at identifying the factors influencing people's decisions on land use and forest resource utilisation, and to provide some preliminary biophysical information. It was found that 93% of local landholders predominantly use low "restinga" sites, and that the major reason for forest fallows is to recover soil fertility. Furthermore, forest conversion and re-conversion processes are a function of community age and parcel size. Over 50% of landholders manage their forest fallows mainly to encourage two tree species: Calycophyllum spruceanum (capiro na) and Cedrela odorata (cedro). The results of this study are encouraging to promote local forests fallows management plans.